Energy for two: New archaeal lineages and the origin of mitochondria. (24th June 2016) - Martin, William F.; Neukirchen, Sinje; Zimorski, Verena; Gould, Sven B.; Sousa, Filipa L.
Abstract : Metagenomics bears upon all aspects of microbiology, including our understanding of mitochondrial and eukaryote origin. Recently, ribosomal protein phylogenies show the eukaryote host lineage – the archaeal lineage that acquired the mitochondrion – to branch within the archaea. Metagenomic studies are now uncovering new archaeal lineages that branch more closely to the host than any cultivated archaea do. But how do they grow? Carbon and energy metabolism as pieced together from metagenome assemblies of these new archaeal lineages, such as the Deep Sea Archaeal Group (including Lokiarchaeota) and Bathyarchaeota, do not match the physiology of any cultivated microbes. Understanding how these new lineages live in their environment is important, and might hold clues about how mitochondria arose and how the eukaryotic lineage got started. Here we look at these exciting new metagenomic studies, what they say about archaeal physiology in modern environments, how they impact views on host‐mitochondrion physiological interactions at eukaryote origin. Abstract : Newly identified archaeal lineages make their living in the utter darkness of black‐smoker‐land on the sea bed using a uniquely ancient mechanism: Methanogenesis in the context of their hydrogen‐dependent energy metabolism. Molecular phylogenetics increasingly suggests that, these are the successors of ancient archaea that teamed up with alpha‐proteobacterium to produce the first eukaryotes; and their thirst for hydrogen gives us clues as to the physiological interaction between host and proto‐mitochondrion.